Optimal Duration of Neoadjuvant Taxane and Carboplatin Combined With Anti-HER2 Targeted Therapy for HER2-Positive Breast Cancer - Xie, Yifan; Wu, Siyu; Zhang, Ying; Li, Jianwei; Mo, Miao; Shao, Zhimin; Liu, Guangyu (Frontiers in Oncology, 2021)
Background: Taxane, carboplatin and trastuzumab (TCH) is an effective neoadjuvant regimen for human epidermal growth factor receptor 2 (HER2)-positive breast cancer with high pathologic complete response (pCR) rate. The KATHERINE trial changes the outlook for high-risk HER2-positive breast cancer, which suggests that escalation treatment for patients with residual disease after neoadjuvant anti-HER2 therapy may improve survival. The major objective of this study was to investigate the fewest cycles of neoadjuvant TCH therapy needed to screen out non-pCR patients in the KATHERINE era. Methods: This retrospective study included patients with HER2-positive breast cancer who received either four or six cycles of TCH preoperatively at Fudan University Shanghai Cancer Center between 2008 and 2019. The pCR status was evaluated, and relevant factors associated with pCR were identified using univariate and multivariable analyses. The pathological results of core needle biopsy (CNB) in the breast tumor after two cycles of neoadjuvant chemotherapy were also collected. Kaplan-Meier curve was used to estimate the event-free survival (EFS). Results: Of 758 eligible patients, 303 were included and analyzed in the four-cycle group and 455 in the six-cycle group. There was no significant difference between the two groups in terms of the pCR rate (46.5% [95%CI, 40.9%-52.2%] in the four-cycle group and 49.9% [95%CI, 45.3%-54.5%] in the six-cycle group, p=0.365) or the five-year EFS (90.4% in four-cycle group and 93.4% in six-cycle group; p=0.871). Multivariable analysis indicated that a negative hormone receptor status and the weekly treatment schedule were independent factors for predicting pCR. After adjusting for factors in the multivariable analysis, there was still no significant difference between four and six cycles of neoadjuvant TCH (OR=1.252, 95% CI 0.904-1.733, p=0.176). Furthermore, 17.9% patients with invasive carcinoma on CNB after two cycles of TCH ultimately achieved pCR in the breast after the completion of neoadjuvant treatment. Conclusion: Four cycles of taxane/carboplatin-based neoadjuvant anti-HER2 therapy may be applied as an optimal treatment duration for screening high-risk HER2-positive breast cancer patients for escalation treatment. Further prospective study is warranted.